The Behavioural Biology of Zoo Animals - Rose, Paul (Taylor & Francis, 2022)
This is the first book on captive animal behaviour, applied to welfare. It enables all aspects of zoo husbandry and management (nutrition, enclosure design, handling & training, enrichment, population management) to be based on a sound knowledge of the species, its evolutionary and natural history.